1998
DOI: 10.1006/dbio.1997.8833
|View full text |Cite
|
Sign up to set email alerts
|

ThemuscleblindGene Participates in the Organization of Z-Bands and Epidermal Attachments ofDrosophilaMuscles and Is Regulated byDmef2

Abstract: We report the embryonic phenotype of muscleblind (mbl), a recently described Drosophila gene involved in terminal differentiation of adult ommatidia. mbl is a nuclear protein expressed late in the embryo in pharyngeal, visceral, and somatic muscles, the ventral nerve cord, and the larval photoreceptor system. All three mbl alleles studied exhibit a lethal phenotype and die as stage 17 embryos or first instar larvae. These larvae are partially paralyzed, show a characteristically contracted abdomen, and lack st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
125
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 140 publications
(130 citation statements)
references
References 55 publications
5
125
0
Order By: Relevance
“…includes abnormalities in both muscle development and photoreceptor differentiation (Begemann et al, 1997;Artero et al, 1998). Vertebrate MBNL(s) also have a role in muscle, because the sequestration of MBNL proteins through binding to CTG repeat expansions is associated with myotonic dystrophies in both human patients (Mankodi et al, 2001) and experimental animal models (Kanadia et al, 2003a).…”
Section: C) E-jmentioning
confidence: 99%
See 1 more Smart Citation
“…includes abnormalities in both muscle development and photoreceptor differentiation (Begemann et al, 1997;Artero et al, 1998). Vertebrate MBNL(s) also have a role in muscle, because the sequestration of MBNL proteins through binding to CTG repeat expansions is associated with myotonic dystrophies in both human patients (Mankodi et al, 2001) and experimental animal models (Kanadia et al, 2003a).…”
Section: C) E-jmentioning
confidence: 99%
“…Muscleblind (MBL) was first characterized in Drosophila, in which it is required cell-autonomously for the development of both muscle and photoreceptors (Begemann et al, 1997;Artero et al, 1998). MBL mutant flies show absence of Z-bands in the sarcomeric apparatus of muscle cells, accompanied by a decrease of extracellular tendon matrix at attachment sites to the epidermis.…”
Section: Introductionmentioning
confidence: 99%
“…Drosophila melanogaster Muscleblind (Mbl) is a nuclear, Cys3His zinc finger protein expressed late in larval development and required for terminal differentiation of muscle and photoreceptor cells [1,2]. The Muscleblind family of proteins spreads across the phylogenetic tree from Drosophila to humans [3].…”
Section: Introductionmentioning
confidence: 99%
“…(17) Discussion Mammalian MBNL proteins have been implicated in muscle differentiation based on their homology to muscleblind, a Drosophila protein required for terminal muscle differentiation in flies. (18) The existence of three MBNL genes in vertebrates as opposed to a single gene in Drosophila implies that there are functional differences between the three mammalian MBNL proteins MBNL1, MBNL2, and MBNL3. While MBNL1 is thought to promote muscle differentiation, we found that MBNL3 acts in an opposing manner and inhibits muscle differentiation.…”
mentioning
confidence: 99%